If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -3x + 20 = 4x + 53 Reorder the terms: 20 + 10x + -3x = 4x + 53 Combine like terms: 10x + -3x = 7x 20 + 7x = 4x + 53 Reorder the terms: 20 + 7x = 53 + 4x Solving 20 + 7x = 53 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 20 + 7x + -4x = 53 + 4x + -4x Combine like terms: 7x + -4x = 3x 20 + 3x = 53 + 4x + -4x Combine like terms: 4x + -4x = 0 20 + 3x = 53 + 0 20 + 3x = 53 Add '-20' to each side of the equation. 20 + -20 + 3x = 53 + -20 Combine like terms: 20 + -20 = 0 0 + 3x = 53 + -20 3x = 53 + -20 Combine like terms: 53 + -20 = 33 3x = 33 Divide each side by '3'. x = 11 Simplifying x = 11
| 3(5.4n+1)+5.6n=26.5 | | b/17-7b/17=12/17 | | 6b-2=10+3b | | -9(2-8)+4x+10=229 | | 8=3-5x | | 1+6x+5x=100 | | 7x(2+8)= | | -y=3x+6 | | -y^3x-2x^4y^3= | | 2y^2+4y-1=7y^2-7y+1 | | 378=(15+x)(12+x) | | d+99999999999999999990=999999999999999999 | | x+(x*4)=4 | | 12-2x=3x+22 | | 3.4c-1.2c=8.8 | | x-4/3+1=7/6 | | 5m+18=15-24-4m | | -k+2=-2k-2-4 | | 9(b+7)=9(b-5) | | 1(23)(-18)(2)= | | Y-39=-39 | | 8k-4k-8= | | (1)(23)(-18)(2)= | | 2-6j+8j=-2j-10 | | 8y-8-3y=12y-6 | | -5(r+9)=-53 | | 9(o+2)=3(o-2) | | 5.7+1.8n=0.84 | | 5d=9d-20 | | 15k^2-8=-2k | | 8-6x+x=2-3x | | 9-5z=12-6z+7 |